Making defense planning meaningful: the evolution of strategic guidance in the Hungarian Ministry of Defense. Issue 4 (1st October 2016) - Nemeth, Bence
ABSTRACT: Hungary, a former communist state, adapted a Western-style defense planning system during the 1990s and 2000s. Although on the surface the elements of this planning system were similar to the planning programming budgeting system (PPBS) developed by the US Department of Defense, strategic guidance for defense planning has not been properly developed until recently. Thus, albeit PPBS-based defense plans were developed in the Hungarian Ministry of Defense (Hungarian MoD) regularly, they lacked both an expression of clear priorities and strategic focus. This article delineates the evolution of strategic guidance in the Hungarian MoD concentrating on current developments, and introduces the newly elaborated analytical concepts and tools, which helped to create needed strategic guidance in Hungary.